Respons Peternak Domba terhadap Penyuluhan Inovasi Aplikasi Analisis Usaha dan Recording Ternak Domba - Bambang Sudarmanto; Risma Safira Ellyalithura Lucky; Supriyanto; Nurdayati (Jurnal Penyuluhan, 2022)
The development of information technology has contributed a lot in the field of agriculture, there are many applications designed to facilitate farmers. In order to find out whether the designed application can be adopted or utilized by farmers, it is necessary to know the response of farmers to extension activities. The purpose of this study is to determine the response of sheep breeders and the influence of internal factors on the response to innovation in the Application of Business Analysis and Sheep Recording. The research was conducted from 10 May to 10 June 2021 in Tempuran Village, Kaloran District, Temanggung Regency. There were 49 breeders selected by purposive sampling as respondents. Those respondents must be a member of a breeder group, have minimal 10 sheep, have a smartphone, and be able to operate an android smartphone. The data were collected by interview and observation methods. The data were analyzed descriptively to determine the response and multiple linear regression analysis to determine the influence of internal factors on the breeders' response. The results showed that the response is in high category with a value of 2.610. Internal factors that influence the breeders' response are age and education level. Age (X1) has a very significant effect (P<0.01) with a regression coefficient of -3.348. Education level (X2) has a significant effect (P<0.05) on the breeders' response with a regression coefficient of 2.686. Meanwhile, the experience in raising livestock, the number of livestock ownership, and cosmopolitan have no significant effect on the breeders' response.